Secret history: writing the rise of Britain's intelligence services - Ball, S. J. (McGill-Queen's University Press, 2020)
"As John le Carré's fictional intelligence men admit, it was the case histories--constructed narratives serving shifting agendas--that shaped the British intelligence machine, rather than their personal experience of secret operations. Secret History demonstrates that a critical scrutiny of internal 'after action' assessments of intelligence prepared by British officials provides an invaluable and original perspective on the emergence of British intelligence culture over a period stretching from the First World War to the early Cold War. The historical record reflects personal value judgments about what qualified as effective techniques and organization, and even who could rightfully be called an intelligence officer. The history of intelligence thus became a powerful form of self-reinforcing cultural capital. Shining an intense light on the history of Britain's intelligence organizations, Secret History excavates how contemporary myths, misperceptions, and misunderstandings were captured and how they affected the development of British intelligence and the state."--